2013
DOI: 10.1029/2012ja017976
|View full text |Cite
|
Sign up to set email alerts
|

Tidal wind mapping from observations of a meteor radar chain in December 2011

Abstract: [1] This article proposes a technique to map the tidal winds in the mesosphere and lower thermosphere (MLT) region from the observations of a four-station meteor radar chain located at middle-and low-latitudes along the 120 E meridian in the Northern Hemisphere. A 1 month dataset of the horizontal winds in the altitude range of 80-100 km is observed during December 2011. We first decompose the tidal winds into mean, diurnal, semidiurnal, and terdiurnal components for each station. It is found that the diurnal/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 46 publications
3
74
0
Order By: Relevance
“…However, there is a large discrepancy between the winds from FPI and HWM93 at ∼ 250 km. Secondly, the winds at the altitude of ∼ 87 km simultaneously measured from FPI and meteor radar at Beijing (∼ 100 km away from FPI, e.g., Yu et al, 2013) during April-May 2010 are compared with HWM07 (Jiang et al, 2012). The monthly averaged nighttime winds from FPI, meteors, and HWM07 exhibit a similar trend except for some discrepancy in the meridional winds.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…However, there is a large discrepancy between the winds from FPI and HWM93 at ∼ 250 km. Secondly, the winds at the altitude of ∼ 87 km simultaneously measured from FPI and meteor radar at Beijing (∼ 100 km away from FPI, e.g., Yu et al, 2013) during April-May 2010 are compared with HWM07 (Jiang et al, 2012). The monthly averaged nighttime winds from FPI, meteors, and HWM07 exhibit a similar trend except for some discrepancy in the meridional winds.…”
mentioning
confidence: 77%
“…Comparison of the winds from the FPI and a meteor radar 100 km away (Yu et al, 2013) with HWM07 shows that, although the meridional wind from FPI has a similar trend as that from meteor radar, the observed FPI and meteor radar winds are weaker than the wind from HWM07 (Fig. 4 of Jiang et al, 2012).…”
Section: Midnight Winds At ∼ 87 Kmmentioning
confidence: 99%
“…Figure 6 shows a strong semidiurnal tide, which is a common feature in winter at northern mid-latitudes (Yue et al, 2010). Using the 4-station meteor radar chain dataset along the 120 • E meridian in the Northern Hemisphere in December 2011, Yu et al (2013) found that the semidiurnal tide dominates at northern mid-latitudes in the height range of 80-100 km with a peak around 96 km. Fechine et al (2009) reported a mesospheric bore propagating in a Doppler wind duct that was associated with a semidiurnal tidal oscillation in the meteor radar wind.…”
Section: Propagation Environment Of the Bore Eventmentioning
confidence: 99%
“…The peak meteor altitudes are around 90 km. In general, Meteor Radar has continuous time coverage and the meteor wind data are of high quality, as demonstrated by many previous studies (Zhao et al, 2005a,b;Yu et al, 2013). In this study, we used wind data acquired at 87 km and 97 km with a time resolution of 1 h for the period from August 2011 until April 2014.…”
Section: Data Collection Processmentioning
confidence: 83%
“…A Meteor Radar chain of four stations was gradually established over several years along the 120°E meridian in the northern hemisphere by the Institute of Geology and Geophysics, Chinese Academy of Sciences (IGGCAS). These radars are used for studying tidal structures in the upper atmospheric wind at altitudes of 80-100 km (Xiong et al 2004;Zhao et al, 2005a,b;Yu et al, 2013). For the F-region wind, Liu et al (2003a) developed a new approach to derive the vertical component equivalent wind (VEW) from ionosonde measurements, before investigating the climatology of VEW over Wuhan (114.4°E, 30.6°N) and then expanding it to global change (Liu et al, 2003b(Liu et al, ,c, 2004Luan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%